PENGENALAN PAHLAWAN SAM RATULANGI PADA SISWA MI/SD - Khairunnisa, Hilda Zuhri; Fuadah Z, Anis (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2020)
This article moots about a struggle of a famous and an influenced figure ever in that time, coming from Minahasa, North Sulawesi. He fought for Indonesia in his own way and got his thoughts gone viral even until now. His name is Gerungan Saul Samuel Jacob Ratulangi or usually called Sam Ratulangi. He also had the biggest role why Indonesia nowadays is called â€œIndonesiaâ€. This article was made to 1) acquaint a biography of a patriot that is Gerungan Saul Samuel Jacob Ratulangi to learners, especially in elementary school. 2) acquaint the values in Sam Ratulangi. 3) know how Sam Ratulangi fought for his beloved country and what was his role in defending Indonesia. 4) acquaint his thoughts that is going viral even in nowadays. All of the data are gotten from books, literature, and journals that are related to the topic.